PENANAMAN KARAKTER CINTA ALAM DALAM KEHIDUPAN SOSIAL MASYARAKAT MELALUI ORGANISASI WONGSALAM (WONGSENENGALAM) - Hanifah Fitriyani; Atiqa Sabardila (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe the inculcation of the character of love of nature in the social life of the community through the Wongsalam (Wongsenengalam) organization. The research data is in the form of descriptive text that presents the planting of the character of love for nature. Sources of data were obtained by observing, documenting activities, followed by interviews with the chairman and several members, and the last technique was taking notes. The analysis used in the study is in the form of an analysis of strengths, weaknesses, opportunities, threats or commonly called a SWOT analysis. The results of the study show that there are goals in instilling the character of love for nature through: 1) a close sense of solidarity, 2) conveying knowledge about work programs about the importance of caring for the environment and the natural environment, and 3) exemplary protecting nature and the surrounding environment. Research shows that the goals of the Wongsalam organization have a positive impact on its members and get a good response from the surrounding community. Not only that, in addition to gaining useful knowledge at the Wongsalam organization, members can also help preserve nature and help the surrounding community.